2003
DOI: 10.1002/jbm.b.10074
|View full text |Cite
|
Sign up to set email alerts
|

Tendon surface modification by chemically modified HA coating after flexor digitorum profundus tendon repair

Abstract: Carbodiimide derivatized HA (cd-HA) is less soluble in water than normal HA, and therefore has an increased tissue residence time. The purpose of this study was to study the effect of cd-HA gel on gliding and repair integrity during simulated repetitive motion of a repaired tendon in vitro. A total of 36 flexor digitorum profundus (FDP) tendons from six adult mongrel dogs were used and divided into three groups of control, simple HA, and cd-HA. The gliding resistance between the FDP and the proximal pulley, FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Tendon surface modifications using gelatin and hyaluronic acid have been developed to reduce the gliding resistance of both tendon graft and repaired tendon. 27,28,30 Here we investigate the effect of adding lubricin to these formulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendon surface modifications using gelatin and hyaluronic acid have been developed to reduce the gliding resistance of both tendon graft and repaired tendon. 27,28,30 Here we investigate the effect of adding lubricin to these formulations.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 A number of abnormalities in the function of tendons within tenosynovial sheaths, and tendon adhesion formation, have also been described in CACP syndrome, suggesting that lubricin is an important element necessary for normal tendon function. 25 Previous studies have looked at the effect of hyaluronic acid and gelatin on the gliding resistance 14,26-28 and outcome of tendon repairs. 29-33 The purpose of the current study was to investigate the effect of the addition of lubricin to existing tendon surface modifications on the gliding resistance of repaired flexor tendon after 1,000 cycles of tendon motion in a canine model in vitro.…”
mentioning
confidence: 99%
“…This modification of hyaluronic acid is believed to decrease water solubility, increase binding strength, and therefore increase tissue residence time 40 . Recent reports on carbodiimide-modified hyaluronic acid combined with gelatin on the surface of extrasynovial tendons noted decreased gliding resistance between the tendon and its pulley system during repeated flexion-extension motion over 500 cycles in a canine model in vitro 41,42 . The purpose of the current study was to investigate whether such a modified extrasynovial tendon, treated with cd-HA, would show improved performance in vivo, as demonstrated by increased tendon gliding ability, decreased digital work of flexion, and reduced adhesion formation.…”
mentioning
confidence: 98%
“…Other authors have supposed that adhesions could be reduced with more stable HA derivatives and HA could be fixed to the tendon surface, and its removal could be minimized [810, 19, 20]. Several HA derivatives have been evaluated.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The carbodiimide-derivatized HA (cd-HA) is less soluble in water than normal HA and therefore has an increased tissue residence time [19, 20]. Preliminary experiments, performed on intact tendon grafts in vitro , showed that the preparation improved gliding and that the effect was increased when gelatin was added [8].…”
Section: Experimental Studiesmentioning
confidence: 99%